2014
DOI: 10.1038/ejcn.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D, APOE ɛ4 genotype and cognitive function: findings from the 1958 British birth cohort

Abstract: Both high and low vitamin D statuses have been associated with lower memory function. Apolipoprotein E (APOE) ɛ4 alleles have been associated with reduced memory function, and separately with higher vitamin D concentrations. This report aims to examine if the presence of APOE ɛ4 alleles contributes to the relationship between vitamin D and memory function. A total of 4848 (46% female) participants from the 1958 British birth cohort had information on APOE genotypes and completed memory tests at 50 years, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…This non-linear association was further described in a recent study investigating the impact of vitamin D concentrations and APOE ε4 carrier status on cognitive function. In this study, researchers demonstrated that ε4 homozygotes with high vitamin D concentrations had higher cognitive functioning and those with low vitamin D concentrations had lower cognitive functioning (60). However, ε4 heterozygotes and non-carriers with high vitamin D concentrations had lower cognitive functioning.…”
Section: Nutrigenomic Considerationsmentioning
confidence: 90%
“…This non-linear association was further described in a recent study investigating the impact of vitamin D concentrations and APOE ε4 carrier status on cognitive function. In this study, researchers demonstrated that ε4 homozygotes with high vitamin D concentrations had higher cognitive functioning and those with low vitamin D concentrations had lower cognitive functioning (60). However, ε4 heterozygotes and non-carriers with high vitamin D concentrations had lower cognitive functioning.…”
Section: Nutrigenomic Considerationsmentioning
confidence: 90%
“…It has been reported that memory status and serum vitamin D concentrations may be modifiable by APOE genotype [50]. Carriers of two APOE-ε4 alleles appear to possess higher memory function with higher vitamin D status than those with zero or one APOE-ε4 allele [50]. These data are from a single study and more evidence is required to determine any true relationship between cognition, vitamin D status and APOE genotype.…”
Section: Genotyping For Apoementioning
confidence: 95%
“…The rare ε2 allele (~7%) is thought to be protective against AD [49]. It has been reported that memory status and serum vitamin D concentrations may be modifiable by APOE genotype [50]. Carriers of two APOE-ε4 alleles appear to possess higher memory function with higher vitamin D status than those with zero or one APOE-ε4 allele [50].…”
Section: Genotyping For Apoementioning
confidence: 99%
“…For example, exercise (71), education (72), and vitamin D status (73) have all been shown to impact the effects of APOE genotype on cognitive functions. Also, lifestyle factors such as alcohol consumption and physical activity were found to significantly interact with APOE genotype in determining plasma lipid concentrations in a gender-specific manner (74).…”
Section: Environmental Stimuli That Influence Apoementioning
confidence: 99%